New era : the magazine that portrays identity and dignity - Sicherman, Carol ([s.n] : Femrite-Uganda Women Writers Association, 1999)
This is issue no. 17 of March, 1999 photocopied from the monthly ma gazine of Femrite-Uganda Women Writers Association
AR/SIC/1/5/5
English
Shelf no. 3
Keywords: Literature; Women